ANALYSIS CONTENT OF ORGANIC MATTER IN SEDIMENT AND ABUNDANCE OF MACROZOOBENTHOS IN TELUK BUO PADANG WEST SUMATERA - Utama, Rinol Putra; Nedi, Syahril; Tanjung, Afrizal (Asian Journal of Aquatic Sciences, 2019)
This research was conducted in May 2018 in the waters of Teluk Buo, Padang, West Sumatra. The purpose of this study was to determine the environmental quality of the Teluk Buo waters, especially to determine the abundance of macrozoobenthos and determine the relationship between sediment organic matter and abundance of macrozoobenthos. The method used in this study is a survey method. The results of the study note that the waters of the Teluk Buo are included in the medium polluted criteria with a diversity index (H ') ranging from 2.18-3.43, dominance index (C) 0.10-0.32 and uniformity index (e) 0.51-0,78. Abundance ranges from 80-240 ind/m2 with the number of macrozoobenthos species found there are 9 species of gastropods and 5 species of bivalves. The relationship of sediment organic matter content to macrozoobenthos abundance was included in the moderate criteria with a correlation coefficient (r) -0.382